Development of Neuropeptide Y and Cell-Penetrating Peptide MAP Adsorbed onto Lipid Nanoparticle Surface - Silva, Sara (2022)
Functionalization of nanoparticles surfaces have been widely used to improve diagnostic and therapeutic biological outcome. Several methods can be applied to modify nanoparticle surface; however, in this article we focus toward a simple and less time-consuming method. We applied an adsorption method on already formulated nanostructured lipid carriers (NLC) to functionalize these nanoparticles with three distinct peptides sequences. We selected a cell-penetrating peptide (CPP), a lysine modified model amphipathic peptide (Lys(N3)-MAP), CPP/drug complex, and the neuropeptide Y. The aim of this work is to evaluate the effect of several parameters such as peptide concentration, different types of NLC, different types of peptides, and incubation medium on the physicochemical proprieties of NLC and determine if adsorption occurs. The preliminary results from zeta potential analysis indicate some evidence that this method was successful in adsorbing three types of peptides onto NLC. Several non-covalent interactions appear to be involved in peptide adsorption with the possibility of three adsorption peptide hypothesis that may occur with NLC in solution. Moreover, and for the first time, in silico docking analysis demonstrated strong interaction between CPP MAP and NPY Y1 receptor with high score values when compared to standard antagonist and NPY.